Palliative care knowledge and attitudes towards end-of-life care of nurses in tertiary hospitals - Eilean R. Lazarus; Joshua K. Muliira; Omar Al-Zaabi; Murtadha K. Al-Khabori; Mudhar M. Al Adawi; Qasim Al Mamari (Curationis)
Background: Efforts to increase access to palliative care (PC) must consider healthcare providers’ level of knowledge and attitude because both affect the quality of services. Nurses play essential roles in the delivery of PC, including end-of-life care.